(untitled) (diségno, 2022)
In recent years, new information and communication technologies have had a significant impact on the design field, also involving, in a relevant way, the design and marketing processes related to product packaging. The multiple roles assumed by packaging, from functional ones to visualization ones aimed at conveying the corporate brand and persuading the buyer, have been enriched with renewed nuances and unprecedented possibilities. The latter have profoundly redefined both the relationships with the product and those with the consumer. This article explores the new ways of communicating packaging and its transition from a simple graphic-formal artefact to an articulated graphic interface. Through the narration of recent experiences that testify its transfig- uration towards advanced forms of communication of products/services, the authors investigate the possibilities offered by new technologies and the founding role of drawing in this specific field of design, in which applications are increasingly characterized by multidisciplinary approaches.